Should vitamin B12 status be considered in assessing risk of neural tube defects? - MOLLOY, ANNE (My University, 2018)
There is a strong biological premise for including vitamin B12 with folic acid in strategies to prevent neural tube defects (NTDs), due to the closely interlinked metabolism of these two vitamins. For example, reduction of B12 deficiency among women of reproductive age could enhance the capacity of folic acid to prevent NTDs by optimizing the cellular uptake and utilization of natural folate cofactors. Vitamin B12 might also have an independent role in NTD prevention, such that adding it in fortification programs might be more effective than fortifying with folic acid alone. Globally, there is ample evidence of widespread vitamin B12 deficiency in low‐ and middle‐income countries, but there is also considerable divergence of vitamin B12 status across regions, likely due to genetic as well as nutritional factors. Here, I consider the evidence that low vitamin B12 status may be an independent factor associated with risk of NTDs, and whether a fortification strategy to improve B12 status would help reduce the prevalence of NTDs. I seek to identify knowledge gaps in this respect and specify research goals that would address these gaps.
PUBLISHED
Keywords: Vitamin B12; Cobalamin; Folic acid; Maternal blood